Operating Logic Improvement of the Fixing Type Automatic Park Brake - N. V. Malikov; A. V. Kazarinov; N. M. Voluyskiy (Вестник Научно-исследовательского института железнодорожного транспорта, 2015)
The paper presents information on the development of a new automatic park brake version hereinafter referred to as action mode AST (URD-AST subsystem) control device. Operating pattern of the fixing type automatic park brake version now in use on the railway rolling stock stipulates its being in the ‘holding mode’ state under conditions of service braking and its transition to the ‘action mode’ state under emergency braking conditions. It has been demonstrated that remote returning process of the automatic park brake into the ‘holding mode’ state must be known controllable. This can be achieved through exercising service braking procedure with fully charged automatic brake of the rolling stock in the complete stop state. Railway reality knows a fair number of cases of the guard’s valve operation with the aim of impeding electric train’s departure. Each time this causes braking action after which train driver has to spend additional time for carrying out the deactivation procedure of the automatic park brake’s ‘action mode’, thus contributing to train schedule disruptions. To prevent such serious implications it is proposed to introduce special-purpose compulsory delay of the AST placement under the ‘action mode’. Such a delay is possible while using the newly developed URD-AST subsystem. This subsystem implements servo-cylinder working cavity charging pattern of the automatic park brake’s fixing unit depending on the pressure level in the electric train brake pipe and on the pressure level in the auxiliary reservoir of the car where it is installed. There are described operating procedure options of the URD-AST subsystem under various control provisions and operating regimes of electric train brakes. Also presented are operational efficiency determinations of the URD-AST subsystem installed on individual railway car. They were obtained in the tests of electric train ED4M-500 at the JSC VNIIZhT Testing Center (Testing Loop). There are demonstrated operational advantages delivered by the proposed device, ensuring on-time performance of electric trains through compulsory delay introduction of the “action mode” deactivation procedure and allowance of this device joint operation with anti-skid devices.